Net Positive Environmental Impact in the Digital period with Special focus to FMCG companies - Gitanjali Singh (International Journal of Modern Agriculture, 2020)
In the current digital era, sustainability is an imperative issue for the economies and companies. Companies are changing their focus from merely â€œdoing less harmâ€ to becoming â€œnet positiveâ€ and creating positive impact in the society. Their endeavour is to inculcate green practices right from supply chain to end user consumption and then applying 3Râ€™s. For this very concern the present study has selected three renowned companies of FMCG sector- HUL Ltd., ITC Ltd., P&G Ltd. These companies portray them as the green marketing companies, comprising green manufacturing, and green supply chain and from their business sustainability reports which are showcased online witnessing a move towards eco environment. Hence, this paper aims to review the strategic moves of these companies, their impact on profitability and to gauge their environmental impact. Results reveal that digitalization has facilitated integration of all business stakeholders kick starting the companies to attain their stated vision.